Micro electro discharge machining of nonconductive ceramic - Ali, Mohammad Yeakub; Sabur, Abdus; Banu, Asfana; Maleque, Md. Abdul; Adesta, Erry Yulian Triblas (Deer Hill Publishing, 2018)
The micro-electro discharge machining (micro-EDM) models established for single spark erosion are not applicable for nonconductive ceramics because of random spalling. Moreover, it is difficult to create single spark on a nonconductive ceramic workpiece when the spark is initiated by the assisting electrode. In this paper, process development for nonconductive zirconium oxide (ZrO2) is discussed. It is shown that the charging and discharging duration depend on the capacitance and resistances of the circuit. The number of sparks per unit time is estimated from the single spark duration derived from heat transfer fundamentals. The model showed that both the capacitance and voltage are significant process parameters for material removal rate (MRR). However, capacitance was found to be the dominating parameter over voltage. As in case of higher capacitances, the creation of a conductive carbonic layer on the machined surface was not stable; the effective window of machining 101 - 103 pF capacitance and 80 - 100 V gap voltage or 10 - 470 pF capacitance and 80 - 110 V gap voltage. This fact was confirmed EDX analysis where the presence of high carbon content was evident. Conversely, the spark was found to be inconsistent using parameters beyond these ranges and consequently insignificant MRR. Nevertheless, the effective numbers of sparks per second were close to the predicted numbers when machining conductive copper material. In addition, higher percentage of ineffective pulses was observed during the machining which eventually reduced the MRR. In case of validation, average deviations between the predicted and experimental values were found to be around 10%.